THE CHANGE OF GHRELIN LEVELS IN INTESTINAL PARASITIC INFECTIONS - Erensoy, Ahmet; Aydin, Suleyman; Kelestimur, Neslihan; Kirbag, Sevda; Kuk, Salih (Sciendo, 2010)
The aim of this work was to examine the relationship between active (acylated ghrelin) and inactive (desacylated ghrelin) ghrelin in the serum and other serum parameters in intestinal parasitic infections and healthy controls. Conventional microscopic methods (saline and iodine solutions, trichrome stain) were used to identify intestinal parasites in stool samples of 29 subjects attending Firat University Hospital. Serum parameters were assessed in a single measurement of serum from 29 parasite subjects, and in 18 healthy controls. Serum acylated ghrelin and desacylated ghrelin levels were measured using a commercial radioimmunoassay (RIA) kit. Paraoxonase and arylesterase were measured by using a spectrophotometer at 405 nm and 270 nm, respectively. Serum concentrations of acylated ghrelin and desacylated ghrelin were more markedly decreased in helminth bearing patients than the control group. Glucose, cholesterol and triglyceride levels were higher in intestinal parasitic infections than in controls. Furthermore, there were no correlations between ghrelin levels and BMI. These results indicate that low ghrelin and PON1/AE level may be important for appetite monitoring in intestinal parasitic infections.
Keywords: serum; active/inactive ghrelin; paraoxonase; arylesterase; parasite